Modeling, simulation and optimization of complex processes: proceedings of the Third International Conference on High Performance Scientific Computing, March 6–10, 2006, Hanoi, Vietnam - Bock, Hans Georg; Kostina, Ekaterina; Rannacher, Rolf (Springer Berlin Heidelberg, 2008)
Development of a Fault Detection Model-Based Controller -- Sensitivity Generation in an Adaptive BDF-Method -- The gVERSE RF Pulse: An Optimal Approach to MRI Pulse Design -- Modelling the Performance of the Gaussian Chemistry Code on x86 Architectures -- Numerical Simulation of the December 26, 2004: Indian Ocean Tsunami -- Approximate Dynamic Programming for Generation of Robustly Stable Feedback Controllers -- Integer Programming Approaches to Access and Backbone IP Network Planning -- An Adaptive Fictitious-Domain Method for Quantitative Studies of Particulate Flows -- Adaptive Sparse Grid Techniques for Data Mining -- On the Stochastic Geometry of Birth-and-Growth Processes. Application to Material Science, Biology and Medicine -- Inverse Problem of Lindenmayer Systems on Branching Structures -- 3D Cloud and Storm Reconstruction from Satellite Image -- Providing Query Assurance for Outsourced Tree-Indexed Data -- An Adaptive Space-Sharing Scheduling Algorithm for PC-Based Clusters -- Fitting Multidimensional Data Using Gradient Penalties and Combination Techniques -- Mathematical Modelling of Chemical Diffusion through Skin using Grid-based PSEs -- Modelling Gene Regulatory Networks Using Galerkin Techniques Based on State Space Aggregation and Sparse Grids -- A Numerical Study of Active-Set and Interior-Point Methods for Bound Constrained Optimization -- Word Similarity In WordNet -- Progress in Global Optimization and Shape Design -- EDF Scheduling Algorithm for Periodic Messages On Switched Ethernet -- Large-Scale Nonlinear Programming for Multi-scenario Optimization -- On the Efficiency of Python for High-Performance Computing: A Case Study Involving Stencil Updates for Partial Differential Equations -- Designing Learning Control that is Close to Instability for Improved Parameter Identification -- Fast Numerical Methods for Simulation of Chemically Reacting Flows in Catalytic Monoliths -- A Deterministic Optimization Approach for Generating Highly Nonlinear Balanced Boolean Functions in Cryptography -- Project-Oriented Scheduler for Cluster Systems -- Optimizing Spring-Damper Design in Human Like Walking that is Asymptotically Stable Without Feedback -- Stability Optimization of Juggling -- Numerical Model of Far Turbulent Wake Behind Towed Body in Linearly Stratified Media -- A New Direction to Parallelize Winograd’s Algorithm on Distributed Memory Computers -- Stability Problems in ODE Estimation -- A Fast, Parallel Performance of Fourth Order Iterative Algorithm on Shared Memory Multiprocessors (SMP) Architecture -- Design and Implementation of a Web Services-Based Framework Using Remoting Patterns -- Simulation of Tsunami and Flash Floods -- Differentiating Fixed Point Iterations with ADOL-C: Gradient Calculation for Fluid Dynamics -- Design Patterns for High-Performance Matrix Computations -- Smoothing and Filling Holes with Dirichlet Boundary Conditions -- Constraint Hierarchy and Stochastic Local Search for Solving Frequency Assignment Problem -- Half-Sweep Algebraic Multigrid (HSAMG) Method Applied to Diffusion Equations -- Solving City Bus Scheduling Problems in Bangkok by Eligen-Algorithm -- Partitioning for High Performance of Predicting Dynamical Behavior of Color Diffusion in Water using 2-D tightly Coupled Neural Cellular Network -- Automatic Information Extraction from the Web: An HMM-Based Approach -- Advanced Wigner Method for Fault Detection and Diagnosis System.
Keywords: Konferenzschrift -- 2006 -- Hanoi; Wissenschaftliches Rechnen